Kajian Penilaian Kontribusi Sektor Pariwisata dalam Mendukung Ekonomi Daerah di Kabupaten Boalemo - Fibriyanti S. Lakoro; Syamsinah, Syamsinah (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
The research objectives are (1) to determine the assessment of the contribution of the tourism sector in supporting the regional economy of Boalemo Regency, (2) the efforts made by the Boalemo Regency Tourism, Youth and Sports Department to support the regional economy of Boalemo Regency. The research method used is qualitative, data collection is carried out by interviews, observation and documentation. The data analysis technique used uses the Miles and Huberman model where data presentation starts from data reduction, data presentation and conclusion or verification. The results of the research are (1) Contribution through the tourism sector really supports the regional economy, but it is not evenly distributed as a whole, but there is some potential with an analysis of the sector's economic growth in each region. (2) The efforts carried out at the Boalemo Regency Tourism, Youth and Sports Office in implementing regional economic improvement through tourism are very necessary for efforts that do not meet the standards of something see, Something to do and Something to buy in synergy within the Regency tourism development community Boalemo.